Transformational School Leadership in Enhancing Teacher Performance - Rizky Ananda (Sufiya Journal of Islamic Studies, 2024)
This study aims to determine the effect of madrasah head leadership on teacher performance at MTs Nurul Iman Tanjung Morawa. The approach used is quantitative with survey method, involving 37 teachers as respondents. The instrument used was a Likert scale questionnaire, and the data were analyzed using a simple regression test. The results showed that there was a significant influence between the leadership of the madrasah head and teacher performance with a significance value of 0.006 <0.05 and a calculated T value of 2.971> T table 2.040. However, the coefficient of determination (R Square) is only 0.216, which indicates that the effect is still relatively low. This finding indicates the need for madrasah principals to strengthen their leadership roles according to transformational leadership indicators, such as providing inspirational motivation, paying attention to teachers' individual needs, creating a shared vision, and encouraging professional development through training, seminars, and active involvement of teachers in the decision-making process.